Understanding social media discontinuance from social cognitive perspective: Evidence from Facebook users. (August 2022) - Fu, Shaoxiong; Li, Hongxiu
Based on social cognitive theory, this study proposes a research framework to investigate two different social media discontinuance behaviours: reduced usage and abandoned usage. Specifically, perceived technology overload, information overload and social overload are the environmental factors that induce negative personal states, including dissatisfaction and social media fatigue, which lead to negative behavioural changes, such as reduced usage and abandoned usage of social media. The proposed research model was tested empirically with data collected among Facebook users. The research results indicate that impacts from perceived technology overload, information overload and social overload on social network fatigue and dissatisfaction vary. Dissatisfaction exerts greater impacts on abandoned-usage behaviour than social media fatigue, but similar impacts on reduced-usage behaviour as social media fatigue. In addition, reduced-usage behaviour was found to lead to abandoned-usage behaviour. Finally, we discuss the theoretical and practical contributions that can be gleaned from the proposed research model.